1994
DOI: 10.1109/23.322789
|View full text |Cite
|
Sign up to set email alerts
|

Photostimulated luminescence and thermoluminescence of LSO scintillators

Abstract: Photostimulated luminescence (PSL) and thermoluminescence (TL) from five L~2(1-~)Ce2~(Si04)0 &SO) crystals with different light outputs is reported. Optical irradiation into the Ce3+ absorption bands causes the appearance of a broad absorption band near 280 nm which is ascribed to Ce4+. In addition, a tail is observed extending beyond 700 nm. Optical irradiation into this tail (PSL) or heating of the crystal (TL) results in Ce3+ emission. It is shown that both PSL and TL are due to the same traps. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…16. Annealing experiments in reducing or oxidizing atmosphere led to the suggestion that traps could be related to oxygen vacancies [136]. Evaluation of trap depths of these peaks shows approximately the same values up to 250 °C; the values are reported in the inset of Fig.…”
Section: Orthosilicate Single Crystalsmentioning
confidence: 76%
“…16. Annealing experiments in reducing or oxidizing atmosphere led to the suggestion that traps could be related to oxygen vacancies [136]. Evaluation of trap depths of these peaks shows approximately the same values up to 250 °C; the values are reported in the inset of Fig.…”
Section: Orthosilicate Single Crystalsmentioning
confidence: 76%
“…6, curve 2). Such dependence in LSO:Ce and LGSO:Ce SCF is more flat (curves 1,4), similar to that in high quality LYSO:Ce SC (curve 3) where the influence of the oxygen vacancies on scintillation processes is strongly diminished [17][18][19][20][21][22].…”
Section: Ly Of Lso:ce and Lgso:ce Scfmentioning
confidence: 83%
“…It is well known, that the oxygen vacancies are most easily created at non-bounded chains between Lu1 and Lu2 positions of LSO host [27,33] and they are responsible for large afterglow of LSO:Ce crystals and decrease of their scintillation LY [17,[19][20][21]. Therefore, we expect that in the case of elimination or strong decreasing the influence of Pb 2 þ flux impurity on the luminescence of Ce 3 þ ions in LSO:Ce SCF, one could possess even better scintillation properties in comparison with SC counterparts.…”
Section: Ly Of Lso:ce and Lgso:ce Scfmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorenbos et al [7] analyzed glow curves recorded in the 300-650 K range, evaluated trap parameters and discussed possible nature of traps. Visser et al [8] observed an anti-correlation between TL intensities (300-730 K) and light yields of their crystals. Low temperature glow curves of two LSO:Ce samples were first published by Lempicki and Glodo [9].…”
Section: Introductionmentioning
confidence: 97%